Pro-Choice Rally at State Building Plaza and Surrounding Area - Watkins, Howard::::::::: (1989)
Musicians singing and entertaining large crowd; Overhead banner reads: "Mobilize FOR WOMEN'S LIVES"; Harriet Wagner in middle